2019
DOI: 10.3390/en12244660
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Heat Transfer Performance of a Multi-Disc Sorption Bed Dedicated for Adsorption Cooling Technology

Abstract: The possibility of implementing the innovative multi-disc sorption bed combined with the heat exchanger into the adsorption cooling technology is investigated experimentally and numerically in the paper. The developed in-house sorption model incorporated into the commercial computational fluid dynamics (CFD) code was applied within the analysis. The research allowed to define the design parameters of the proposed type of the sorption bed and correlate them with basic factors influencing the performance of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…The reference wind speed at the hub height was 11.4 m/s [9]. The Grid Convergence Index (GCI) is recommended by the Fluids Engineering Division of the American Society of Mechanical Engineers as a reliable method for grid independence analysis [36]. The GCI was performed to evaluate the grid independence analysis results from the mesh resolution.…”
Section: Computational Domain and Grid Setupmentioning
confidence: 99%
“…The reference wind speed at the hub height was 11.4 m/s [9]. The Grid Convergence Index (GCI) is recommended by the Fluids Engineering Division of the American Society of Mechanical Engineers as a reliable method for grid independence analysis [36]. The GCI was performed to evaluate the grid independence analysis results from the mesh resolution.…”
Section: Computational Domain and Grid Setupmentioning
confidence: 99%
“…The AI methods can also be successfully used to model multibed chillers with multistage working cycles, in which the interdependence of many parameters determines the total efficiency of the device and the generated cooling capacity [29]. The computational fluid dynamics (CFD) models were elaborated in [30,31] to create and evaluate the novel constructions of adsorption beds. The numerical analyses of the finned heat exchanger geometries were carried out in [32,33] in order to improve the heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the CFD simulation showed that the heat transfer performance of a heat plate is improved under various conditions, and the correctness of the model was verified by the experimental results. Marcin Sosnowski et al [22] investigated the possibility of implementing an innovative multidisc sorption bed combined with a heat exchanger into adsorption cooling technology experimentally and numerically, and they incorporated a sorption model developed in-house into the commercial CFD code in the analysis [23].…”
Section: Introductionmentioning
confidence: 99%